Obstacles to the mobilization of rights in cases of prisoner defense in Chile - Jörg Alfred Stippel; Paula Carolina Medina; Rodrigo Lillo (Revista Brasileira de Direito Processual Penal)
A decade ago, the Chilean Public Defense started a program of prison litigation. This article investigates institutional factors that may have an impact on the mobilization of the rights of persons deprived of their liberty. We wonder if the attention provided by the public service mirrors faithfully the demand for defense expressed by convicted persons, or if it responds to institutional policy decisions taken by the Public Defense office that outline or shape such demand? We are looking for institutional factors that determine the selectivity and activation of rights inside prisons. Our analysis starts describing the general public defense services provided to convicted prisoners, paying special attention to violations of constitutional and human rights caused by prison conditions and intra-prison violence. For our analysis, we used quantitative (statistics of the Prisoner Defense) and qualitative information (interviews with key actors). We found that factors associated with the organizational structure, as well as the professional practice of prison defenders, contribute to the fact that the matters handled by the Public Defense end up mirroring the indicators and standards predetermined by the Public Service, giving less importance to situations such as mistreatment, torture, intra-prison violence and inhumane living conditions. We conclude that this selectivity in mobilizing the rights of convicted prisoners violates their constitutional guarantees and, therefore, the institutional objectives of the Prison Defense Service itself.